2018
DOI: 10.1002/wps.20526
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence to favor specific preventive interventions in psychosis: a network meta‐analysis

Abstract: Preventing psychosis in patients at clinical high risk may be a promising avenue for pre-emptively ameliorating outcomes of the most severe psychiatric disorder. However, information on how each preventive intervention fares against other currently available treatment options remains unavailable. The aim of the current study was to quantify the consistency and magnitude of effects of specific preventive interventions for psychosis, comparing different treatments in a network meta-analysis. PsycINFO, Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
189
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 200 publications
(194 citation statements)
references
References 110 publications
(166 reference statements)
5
189
0
Order By: Relevance
“…No meta‐analyses directly compared nutrient supplementation to psychotropic medications. All studies were placebo‐controlled.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No meta‐analyses directly compared nutrient supplementation to psychotropic medications. All studies were placebo‐controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Specific psychiatric conditions (and reported outcomes) considered in this meta‐review included: schizophrenia (examining total symptoms along with positive, negative, general and depressive symptoms, and tardive dyskinesia); states at risk for psychosis (examining attenuated psychosis symptoms, negative symptoms, transition to psychosis, and functioning); depressive disorders (including any clinical depression, diagnosed major depressive disorder (MDD), depression in pregnancy, in old age, or as a comorbidity to chronic health conditions); anxiety and stress‐related conditions (including generalized anxiety disorder, obsessive‐compulsive disorder (OCD) and trichotillomania); bipolar disorder type I and II (examining overall symptoms, bipolar mania, bipolar depression, functional impairments, and quality of life); and ADHD (including composite symptoms, hyperactivity‐impulsivity, inattention, behavioural comorbidities such as aggression, and cognitive functioning).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UHR/CHR programme, although an indicated prevention strategy, arguably meets some of these principles to a degree; yet it fails to meet the most essential criterion: availability of effective treatment for disease prevention. The most recent network meta-analysis of all randomised controlled trials of pharmacological and non-pharmacological interventions for UHR/CHR showed no evidence for specific effect of any intervention, including needs-based treatment (also placebo), in preventing ‘transition’ to psychosis 13. The authors discussed that these recent findings, contradicting the early meta-analyses that reported a positive effect, are mainly driven by the non-significant findings from more recent trials.…”
Section: Is There An Available Therapeutic Intervention That Can Prevmentioning
confidence: 89%
“…The most consistent evidence is from trials of specialist EIP care versus treatment as usual, which shows better short‐to‐medium clinical and functional outcomes for those receiving EIP care, as well as cost‐effectiveness of EIP, while the evidence of specific effective CHR/UHR interventions to prevent the emergence of psychosis remains unclear.…”
mentioning
confidence: 99%